Spain : report by Clement Attlee on interview with the Prime Minister, Foreign Secretary and Mr Greenwood, with regard to their visit to Rome - Chamberlain, Neville, 1869-1940 ; Greenwood, Arthur, 1880-1954 ; Halifax, Edward Frederick Lindley Wood, Earl of, 1881-1959; Attlee, Clement, 1883-1967
1939-01-24 011-0003-002 292/946/11/3(ii)